RED BLOOD CELL ADAPTATIONS INDUCED BY EXERCISE - Stefanović, Radoš; Ristić, Biljana; Drvenica, Ivana (Srpski medicinski časopis Lekarske komore, 2024)
Exercise significantly increases blood flow and perfusion in active muscles to enhance oxygen and nutrient delivery. These enhanced demands affect blood rheology and red blood cell (RBC) characteristics, leading to specific adaptations. These adaptations are influenced by exercise type, intensity, frequency, duration, and individual characteristics of subject population (gender, age, nutritional status etc.).This review aims to comprehensively summarize the different adaptations of erythrocytes to short-term and long-term exercise, as well as the mechanisms of their occurrence, considering the influence of various factors.The results from the previous research indicate that regular exercise enhances the metabolic, structural, and functional capabilities of RBCs. These adaptations include improved energy balance, increased cell turnover rate, improved membrane stability, as well as better antioxidative defense. Despite potential risks such as "sports anemia", exercise also affects the dynamics of hemoglobin and iron concentrations, as well as the appearance of extracellular hemoglobin. Overall, the literature highlights the critical role of exercise in maintaining optimal erythrocyte function, improving circulation, and overall health, offering potential therapeutic benefits.Through a critical review of literature data on the influence of exercise on the characteristics and functions of erythrocytes, this paper can be a useful guideline for the interpretation of clinically significant results in physically active individuals.
Keywords: erythrocytes; training; deformability; erythropoiesis; hemorheology